2017
DOI: 10.1016/j.psychres.2017.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold body dysmorphic disorder in adolescents: Prevalence and impact

Abstract: The aim of the current study was to establish the prevalence of subthreshold body dysmorphic disorder (subthreshold-BDD) in a community sample of adolescents, and to compare disorder correlates in individuals with subthreshold-BDD to those with probable full-syndrome BDD (probable-BDD) and those without BDD (non-BDD). Self-report questionnaires assessing DSM-IV BDD criteria, past mental health service use, and symptoms of body dysmorphic disorder, anxiety, depression, obsessive-compulsive disorder and eating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…With these criteria, it was found that 3.45% of the adolescents showed subthreshold BDD symptomatology, and therefore, were at risk of this disorder. This percentage is similar to what was reported by Schneider et al () who found that 3.4% of Australian adolescents of both sexes had subthreshold BDD symptoms, but lower than the 9% found by Mastro et al () and 7.4% identified by Longley et al (), who based it on a single test for detecting risk of BDD and was probably overestimated.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With these criteria, it was found that 3.45% of the adolescents showed subthreshold BDD symptomatology, and therefore, were at risk of this disorder. This percentage is similar to what was reported by Schneider et al () who found that 3.4% of Australian adolescents of both sexes had subthreshold BDD symptoms, but lower than the 9% found by Mastro et al () and 7.4% identified by Longley et al (), who based it on a single test for detecting risk of BDD and was probably overestimated.…”
Section: Discussionsupporting
confidence: 89%
“…Buhlmann et al, ), although, among participants in the general population who meet subthreshold criteria related to this disorder, there seems to be higher frequency of these indicators among women (e.g. Schieber et al, ; Schneider et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young adults have been indicated to be the most active users on SNS, with findings from the present study showing that females spend more time online (Murray, Maras & Goldfield, 2016;Smith & Anderson, 2018). Consistent with this, recent research has demonstrated that the prevalence of subthreshold BDD is significantly higher in older adolescents, in addition to being more predominant in females (Schneider, Mond, Turner & Hudson, 2017), indicating frequent SNS use as a potential risk factor in the development of BDD in consideration of prevalence levels. It is noted however, that whilst subthreshold disorders do not meet full diagnostic criteria, they do involve the presence of core symptoms and impairment, which has been shown to predict clinical manifestations of the disorder (Wolitzky-Taylor, Dour, Zinbarg, Mineka, Vrshek-Schallhorn, Epstein et al, 2014).…”
Section: Discussionsupporting
confidence: 58%
“…Subclinical or subthreshold BDD symptoms are more prevalent again, with 3.4% of adolescents reporting dysmorphic concerns that cause distress or impairment (Schneider, Mond, Turner, & Hudson, 2017b). These subclinical BDD symptoms are associated with high levels of anxiety and depression, and reduced quality of life, suggesting that even milder forms of BDD preoccupation do not represent a normal level of appearance concern (Schneider et al, 2017b). What remains unknown at present is the course of milder BDD symptoms over time.…”
mentioning
confidence: 99%